Iceland : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2002)
This 2002 Article IV Consultation highlights that the economic developments in Iceland since early 2001 have been characterized by progress in the correction of some of the imbalances. As sentiment turned, the currency depreciated sharply and growth in economic activity decelerated from 5 1\2 percent in 2000 to 3 percent in 2001-bringing it closer to its long-term sustainable pace. The balance of demand switched swiftly from consumption and other domestic expenditure to net exports and, as a result, the current account deficit fell to about 4 1\2 percent of GDP.